Indian Migrant Workers' Experience During the COVID-19 Pandemic Nationwide Lockdown. (August 2022) - Kumar, Navin; Udah, Hyacinth; Francis, Abraham; Singh, Sanchita; Wilson, Anica
This article explores the lived experiences of some Indian migrant workers (MW) during the first COVID-19 pandemic nationwide lockdown, investigating their plights from a social identity perspective. It analyses crises associated with the COVID-19 pandemic, and with hunger and starvation. Drawing on a qualitative study conducted with twelve participants in the city of Pune in the Western Indian state of Maharashtra, the findings suggest that the participants' plights have been exacerbated by the COVID-19 pandemic. The findings indicate the need for policy responses to focus on addressing conditions of work, terms of employment and access to necessities for Indian MW, including ensuring conditions for a prompt job-ready recovery and mental health care after the COVID-19 pandemic.